Eliminating Collaborative Black-hole Attack by Using Fuzzy Logic in Mobile Ad-hoc Network - Sharma, A; Johari, PK (International Journal of Computer Sciences and Engineering, 2025)
Transmitting data securely counter to the mischievous attacks is always concern as a severe issue in an infrastructure less dynamic network called mobile-ad-hoc-network (MANET). Trust assertion between MANET (mobility) nodes is the major attribute for highly secure execution under dynamic topology deflection and open wireless environment. But the mischievous behavior of nodes weakens the trust level of MANET that drags to an untrusted data delivery. The expansion in maligning attacks due to dynamic nature of MANET causes the excessive energy consumption that result in reduction of network lifetime. Trust parameters are adequate to handle the secure route finding procedure. In this composition we also used Fuzzy logic as trusted tool for mitigating the Collaborative Blackhole attack in MANET. This composition recommends a trusted-fuzzy-ad-hoc routing protocol to upgrade the trust between the nodes in MANET. The recommended method customizes the conventional AODV routing protocol. Mischievous behavior nodes are predicted on the basis of mobility based constraints. The packet sequence number is compatible to the log reports of nearby resident nodes, confirms the reliability to the network establishes the trust that avoids the malicious node generation. The result analysis between the proposed technique with the pre-existent technique regarding the routing overhead, throughput, packet delivery ratio shows the effectiveness of trusted-fuzzy-ad-hoc routing protocol in the secure MANET environment.